SISTEM PEMANFAATAN ENERGI SURYA UNTUK PEMANAS AIR DENGAN MENGGUNAKAN KOLEKTOR PALUNGAN - Fatmawati '; Maksi Ginting; Walfred Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted on  Solar Energy Utilization System  for Water  Heater using Trough Collector.  This research was carried out using  an experimental method by putting in place an opened  trough  collector  that  exposed to sunlight. The highest temperature  of collector produced  was 50,03°C  in  average  with an average temperature of water in the tank was 40,07°C at 1 PM, while the lowest temperature of collector was 39,14°C in  average with an average temperature of water  in the tank was  35,28°C at  10 AM.  The highest temperature of collector occured  at 1  PM, because  the intensity of solar radiation  at the time  reached  the  maximum  value.  The experimental results showed  that  the higher  the  intensity of solar radiation,  the higher the temperature of the water produced. The  temperature  of collector  was  also influenced  by  loss  heat of the collector  conduction.  The highest loss  heat by conduction  was 29,05  W at  1 PM, while the lowest loss heat by conduction was 16,85 W at 10 AM.